ДОСЛІДЖЕННЯ РОЗПОДІЛУ ЕЛЕКТРОМАГНІТНОГО ПОЛЯ ТА ТЕМПЕРАТУРИ В ТОРЦЕВІЙ ЗОНІ ОСЕРДЯ СТАТОРА ТУРБОГЕНЕРАТОРА - Кенсицький, О.Г.; Крамарський, В.А.; Кобзар, К.О.; Хвалін, Д.І. (Інститут електродинаміки Національної академії наук України, 2018)
With help a field mathematical model the distribution of electromagnetic field and temperature in a stator core end zone of turbogenerator under load conditions at a different power factor including the conditions of reactive power consumption is investigated. The calculation is carried out not only on the surface, but also in the whole generator end-zone, as well as inside the end and main core packets. Study results of distribution the magnetic induction in a machine end part are given. The average and maximum temperatures ​​for a stator core end packets, press fingers, electromagnetic screen and press plate are determined. Redistribution of maximum magnetic induction and temperature for changes the conditions also was shown. References 9, figures 6, tables 2.